Naples, City of War: 1940-1948. An Urban Catastrophe Across Photography, Cinema, and Architecture - Francesca Capano (Histories of Postwar Architecture)
As it is well-known, Naples was bombed by the Allies between 1940 and 1944 to liberate the city from Nazi occupation. As described by its 16th-century visitors, it was a distinctive and characteristic city whose peculiarities made it a symbol of scenic beauty yet contradictions. Indeed, it is no coincidence that the second episode of Paisà, by Roberto Rossellini (1946), was Napoli. The city is as much a protagonist as the two characters in the story; even though the episode is set in the years of the American occupation, it is portrayed by the director as a city still at war. It was the age of Neorealism, and Rossellini, one of its protagonists, carefully chose the places where to set his story. Focusing on the exteriors, the port, Piazza Mercato, clearly bombed yet perfectly recognizable by the Carmine bell tower, an extraordinary landmark – an example of Neapolitan cultural contaminations – , and the tuff caves, first air-raid shelters and then homes for the displaced, the senzatutto (wholeless, lit. lacking everything), the name often used for those who lost everything and often their families in the bombings. Shortly before Rossellini, the city depicted in Federico Patellani’s photos seemed unaware of the tragedy that would soon befall it despite being about to enter the war. Naples is an icon for both the photojournalist and the filmmaker, both before and after.